Lemon-derived nanovesicles facilitate trans-kingdom transfer of lncRNAs to human cells - Tinnirello, Vincenza; Gasparro, Roberta; Duca, Giulia; Miozzi, Laura; Rotunno, Silvia; Mercati, Francesco; Conigliaro, Alice; Alessandro, Riccardo; Raimondo, Stefania (Frontiers in Molecular Biosciences, 2025)
Plant-derived nanovesicles (PDNVs) are emerging as a novel class of biological messengers, capable of crossing biological barriers and transferring bioactive molecules to human cells. We have previously isolated and characterized nanovesicles from lemon juice (LNVs) that interact with human cells, modulating the mechanisms of oxidative stress and inflammation. However, the mechanisms through which LNVs exert their effect are still poorly understood. Extensive researches have been conducted on the microRNA content of PDNVs, however the profile and role of long noncoding RNAs (lncRNAs) within the vesicles remain unexplored still. In the present study, the lncRNA cargo of LNVs and its role was investigated; highly conserved lncRNAs among Citrus species was highlighted, with a notable enrichment of LM_XLOC_013494 within the vesicles. The lncRNA was successfully transferred to human hepatic (THLE-2) and intestinal (CACO-2) cells treated with LNVs, as confirmed by RT-qPCR and RNA in situ hybridization. Bioinformatic prediction analyses coupled with experimental validation revealed that the isolated lncRNA acts as a molecular sponge, specifically targeting human miR-181b-3p and miR-4420. Importantly, LNV-treated cells showed a statistically significant downregulation of these miRNAs (p ≤ 0.05), suggesting a cross-kingdom regulatory role for the plant lncRNA in modulating human gene expression. Overall, to our knowledge, this study provides novel insights into the trans-kingdom transfer of plant-derived lncRNAs, expanding upon previous findings and offering new experimental evidence.